Determinación del efecto de un tratamiento térmico de normalizado sobre la vida a fatiga por flexión rotativa de un acero AISI 1045 - Hernán Ulloa (Revista INGENIERÍA UC, 2017)
In this research, the e ff ect of a normalized thermal treatment on the fatigue life by rotating flexure of an AISI 1045 steel was determined. For this, the mechanical properties of the normalized steel were defined by tensile tests and five groups of specimens were studied under fatigue at the same level Of alternating stress exceeding the fatigue limit of the material. A control group was used in which it was tested until fracture to determine the failure probability interval by the Maennig method. The other groups were tested with an interruption to perform a normalized, three of them were cycled values lower than the 1 % probability of failure and one slightly above it. Each group was determined the failure probability interval and compared to the control group, a variation of the same was found. With the quantification of these results, we can talk about the possibility of reversion of accumulated fatigue damage, at a number of cycles lower than the 1 % probability of failure, which could be used to extend life fatigue AISI 1045 steel.